Comparison of Short-Term Results between Patients Undergoing Coronary Artery Bypass Graft with a Stent-Placement History and Patients Undergoing Primary Coronary Artery Surgery - Mehdi Hadadzadeh; Mahdiesadat Mirahmadi; Masoud Mirzaei; Ali Pedarzadeh; Bahram Ghasemzadeh; Ali Akbar Rahimianfar (Journal of Tehran University Heart Center, 2019)
Background: Percutaneous coronary intervention (PCI) has become the first-choice treatment strategy the world over for patients with chronic coronary artery disorders. This study compared the effects of previous PCI procedures on the short-term postoperative results of coronary artery bypass graft surgery (CABG).